The impact of online learning on business and economics students’ motivation during the Covid-19 pandemic - Machado, Maria João; Brasão, Ana; Marques, Maria Isabel; Martins, Helena; Mateus, Américo (Business: Theory and Practice, 2024)
This study aims to contribute to the knowledge about the impact of online education, induced by the Covid-19 pandemic, on the motivation of business and economics students. A survey was conducted with students from three higher education institutions located in Portugal, during the first semester of 2021, and 221 valid answers were obtained. The main contributions are as follows: online learning in the wake of the Covid-19 pandemic decreased students’ motivation, which is contrary to studies on online learning conducted before the pandemic; an association was found between decreased motivation and sharing housing with pets and many people, for which there was no empirical evidence yet; two main determinants of the learning experience that influence students’ motivation were identified, namely decreased learning and increased difficulty of the assessment process.